Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s00394-014-0677-0
|View full text |Cite
|
Sign up to set email alerts
|

Oleic acid modulates mRNA expression of liver X receptor (LXR) and its target genes ABCA1 and SREBP1c in human neutrophils

Abstract: This work presents for the first time evidence that human neutrophils are highly sensitive to OA and provides novel data in support of a protective role of this monounsaturated acid against the activation of neutrophils during inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 47 publications
3
26
0
Order By: Relevance
“…3). As previously reported in human livers27282930313233, SREBP1c expression was significantly decreased in NAFL patients compared to control whereas it was increased in NASH patients compared to NAFL2 (Supplemental Fig. S5f).…”
Section: Resultssupporting
confidence: 83%
“…3). As previously reported in human livers27282930313233, SREBP1c expression was significantly decreased in NAFL patients compared to control whereas it was increased in NASH patients compared to NAFL2 (Supplemental Fig. S5f).…”
Section: Resultssupporting
confidence: 83%
“…It is interesting to note the antinomy existing between cholesterol and oleic acid. Indeed, we showed that oleate rich diet decreased cholesterolemia and it has also been reported that oleate increases the expression of ABCA1 , a key player involved in reverse cholesterol transport, in human neutrophils [14]. Conversely, Scd1 whole body knockout mice fed a low fat high carbohydrate diet (a model of complete oleic acid depletion) displays hypercholesterolemia and cholestasis [53].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that oleic acid could modulate the activity of Liver X Receptors (LXR) in human neutrophils [14]. Moreover, LXR activity is sensitive to fatty acids in vitro [15] and it plays a central role in the hepatic effect of dietary fatty acids on lipogenesis in vivo [16].…”
Section: Introductionmentioning
confidence: 99%
“…OA could stimulate mRNA synthesis of liver X‐receptor alpha (LXRα) in human neutrophils . It can also reduce intracellular lipid levels and inflammatory markers .…”
Section: Knowledge Gaps and Future Directionsmentioning
confidence: 99%
“…It can also reduce intracellular lipid levels and inflammatory markers . Conversely, OA induced hepatic steatosis through the upregulation of p38 signalling in an in vitro model . As a result, a dual effect has been suggested for OA in patients with NAFLD; therefore, future robust human clinical trials are needed in this area.…”
Section: Knowledge Gaps and Future Directionsmentioning
confidence: 99%